Health Literacy as Key to Developing Health Related Welfare in Jigawa State, Nigeria - Amina Abubakar Bashir (UICELL, 2017)
English is the official language in Nigeria and all health information are written in English. However, evidence from our health institutions show that there is inadequate knowledge of essential health matters which is evident in the cases of lifestyle related health conditions. This is believed to be related to people’s health literacy which largely determines how people understand health and illness. Thus, determining the level of health literacy among all civil servants is an important step towards understanding the link between literacy and health outcomes. This study investigated the level of health comprehension in Jigawa state, Nigeria. Specifically, it identified community’s level of comprehension of health information contained in select health materials and further determined the relationship between their levels of comprehension and health perception with a view to providing a framework for designing, implementing and evaluating community health social welfare programmes. Both quantitative and qualitative research methods were used, using a modified Test of Functional Health Literacy among Adults (TOFHLA) and the analysis involved analysing the results with the findings from the quantitative data analysed. It has been found that health comprehension is low in Jigawa state. It has also been found that individual’s ability to read drug labels, interpret dosage instructions, determine health benefits of ingredients in packages of foods and drinks, among others, is determined by their health literacy not withstanding their education. It has been revealed that the respondents do not apply their knowledge of English in comprehending labels on health related products.